Pengaruh Media Tanam dan Dosis Pupuk Kandang Sapi Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Solanum lycopersicum L.) - Sari Susanti; Meli Roslianti; Selviana Anggraini; Feri Agriani (University of Prof. Dr. Hazairin, SH, 2026)
Tomatoes are a type of fruit vegetable that has excellent prospects in agribusiness development due to its high economic value and high nutritional value. The successful growth and yield of tomato plants are greatly influenced by the condition of the planting medium and the availability of nutrients in the soil. The planting medium serves as a place for root attachment and as a provider of nutrients for plants. Therefore, selecting the right dose of organic fertilizer is very important to improve soil quality and support the growth of tomato plants. The purpose of this study was to obtain the best dose of cow manure and various planting media for the growth and yield of tomato plants. This study used a completely randomized design (CRD) with 2 factors. The first factor is the planting medium (M) which is PMK soil (M1) and sandy black soil (M2). The second factor is the dose of cow manure (D) which consists of 500 g/plant (D1), 1000 g/plant (D2), 1500 g/plant (D3) and 2000 g/plant (D4). The observation data were analyzed statistically by analysis of variance (F test). If the calculated F > F table 5%, then the difference between treatments was tested with Duncan's New Multiple Range Test (DNMRT) at a significance level of 5%. The results showed that the application of cow manure with a dose of 2000 g/plant had a significant effect on observations of plant height, number of fruits and fruit weight. The sandy black soil medium had a significant effect on observations of root length, root volume, number of fruits and fruit weight.